Attitudes of sperm donors towards offspring, identity release and extended genetic screening. Issue 4 (October 2021) - Pennings, Guido; Mocanu, Edgar; Herrmann, Janne Rothmar; Skytte, Anne-Bine; Burke, Corey; Pacey, Allan
Abstract: Research question: What is sperm donors' attitude towards offspring, anonymity and extended genetic screening? Design: An online questionnaire for sperm donors was administered at Cryos International in the USA and Denmark between 9 and 30 September 2020. A total of 233 donors (37 in the USA and 196 in Denmark) completed the questionnaire. This study is unique because it was performed in a setting that allows donors to choose to be either ID-release or non-ID-release donors. Results: Most donors had two motives to donate: helping childless people and/or financial compensation. ID-release donors differed significantly from non-ID-release donors in numerous aspects of the donation, including relationships with the offspring, information sharing with others and wanting information about offspring. In general, donors had a very positive attitude towards genetic testing and extended genetic screening. Conclusions: Offering the possibility for donors to be either ID-release or non-ID-release allows more donors to be recruited than if only one option were available. The multiple differences between the two donor types suggests that these are groups with profoundly different attitudes towards donation. The general attitude of donors towards genetic testing and expanded genetic screening is very positive but further studies on the attitude of candidate donors are needed.